A complex linear regression model - Abdul Ghapor Hussin,; Norli Anida Abdullah,; Ibrahim Mohamed, (Universiti Kebangsaan Malaysia, 2010)
This paper gives a comprehensive discussion on complex regression model by extending the idea of regression model to circular variables. Various aspect have been considered such as the biasness of parameters, error assumptions and model checking. The advantage of this approach is that it allows the use of usual technique available in ordinary linear regression for the regression of circular variables. The quality of the estimates and the feasibility of the approach were illustrated via simulation. The model was then applied to the wave direction data.